1996
DOI: 10.1002/(sici)1097-4652(199601)166:1<57::aid-jcp7>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide receptor P2u partially mediates ATP-induced cell cycle progression of aortic smooth muscle cells

Abstract: mRNA of the P2u purinoceptor (or nucleotide receptor) is detected both by polymerase chain reaction or Northern blot analyses in cultured aortic smooth muscle cells. When added to the culture medium of these cells, UTP, a specific ligand of the P2u receptor, induces an increased expression of both immediate-early and delayed-early cell cycle-dependent genes. This induction demonstrates similar features (kinetics, concentration dependence) to those obtained after stimulation of aortic smooth cells by exogenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…The majority of the cells in intact blood vessels are SMC, which occupy most of the media, and are involved in vasoconstriction and vasorelaxation of the vessel. P2Y 2 Rs in SMC mediate the induction of immediate-early and delayed-early cell cycle-dependent genes, consistent with a role for P2Y 2 Rs in vascular proliferation of SMC [20, 21]. A recent study demonstrated that P2Y 2 is the predominant functional receptor that responds to ATP and UTP in rat aortic SMC [22].…”
Section: P2 Receptors In Vascular Cellsmentioning
confidence: 53%
See 4 more Smart Citations
“…The majority of the cells in intact blood vessels are SMC, which occupy most of the media, and are involved in vasoconstriction and vasorelaxation of the vessel. P2Y 2 Rs in SMC mediate the induction of immediate-early and delayed-early cell cycle-dependent genes, consistent with a role for P2Y 2 Rs in vascular proliferation of SMC [20, 21]. A recent study demonstrated that P2Y 2 is the predominant functional receptor that responds to ATP and UTP in rat aortic SMC [22].…”
Section: P2 Receptors In Vascular Cellsmentioning
confidence: 53%
“…Taken together, it seems that the principal receptor mediating UTP/UDP-induced contractile responses in blood vessels might be the P2Y 6 subtype. Other studies have reported the presence of both P2Y 4 and P2Y 6 receptors in rat aortic SMC [21, 28, 29]. P2Y 1 receptors are expressed in SMC of a number of blood vessel types and like their EC counterparts mediate vasodilatation most likely through the activation of K + channels (see [18] for review).…”
Section: P2 Receptors In Vascular Cellsmentioning
confidence: 99%
See 3 more Smart Citations